EVALUASI KEBIJAKAN TENTANG PENGAMPUNAN PAJAK ATAS WAJIB PAJAK USAHA MIKRO KECIL MENENGAH PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Fitri Aprilia; M. Arif Nasution; Husni Thamrin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
Limitations of Micro Small Medium Enterprises (MSMEs, or UMKM) in carrying out taxation obligations make UMKM often disobedient in carrying out their obligations. Non-compliance of taxpayers UMKM can harm them with the emergence of problems in the field of taxation on the business they live. To be able to overcome these problems the government has provided tax forgiveness facilities that can be utilized by UMKM. This study aims to evaluate the policy of Law Number 11 of 2016 concerning Tax Remission, of Small and Medium Enterprises Taxpayer at Tax Office Pratama East Medan. The method used in this research is a mixed research method that combines both qualitative and quantitative methods. The main informant in this research is the UMKM taxpayer and the key informant is the tax officer. The population of this study is the UMKM taxpayer who is in the working area of ​​KPP Pratama Medan Timur with the number of more than 100 people. The sample used Taro Yamane formula with sample number of 97 people who become respondents. The results showed that the implementation of tax pardon on the UMKM taxpayer has run quite well.